Lembaga Jaminan Fidusia: Pasca Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 - Dinata, Ari Wirya (Nagari Law Review; Vol 3 No 2 (2020): Nagari Law Review, 2020)
Fiduciary is one of the guarantees where the debtor has the right to control and take advantage of the goods that are used as fiduciary security objects. Article 15 paragraphs (1), (2), and (3) of Law Number 42 Year 1999 concerning Fiduciary Guarantee regulates the execution mechanism for fiduciary security objects when the fiduciary giver (debtor) experiences breach of promise to the fiduciary recipient (creditor). So far, the execution mechanism for fiduciary security objects regulated in the Act creates legal uncertainty and harms the debtor's rights. Because it gives too much power to the creditor. The imbalance of power relations between debtors and creditors towards the handling of the problem of breach of contract actually causes an injustice in existing fiduciary institutions. The Constitutional Court, through decision number 18 / PUU-XVII / 2019, tries to return the fiduciary institution to the spirit of equilibrium relations between debtors, creditors, and fair fiduciary guarantees. After the decision of the Constitutional Court Number 18 / PUU-XVII / 2019. Has there been a harmonious power relationship between two legal subjects in fiduciary guarantees. This paper examines the pre and post fiduciary guarantee institutions of the Constitutional Court and analyzes the legal consequences that occur. This paper uses a type of juridical-normative research using primary data and primary, secondary and tertiary legal material. While the analysis method uses qualitative methods